Analisis Kinerja Protokol ESP-NOW Sebagai Komunikasi Data Multi-Node Wireless Sensor Network Pada Esp32 dengan IoT Gateway dan Visualisasi Web - Eko Wahyudi; Sandy Suryo Prayogo (TIN: Terapan Informatika Nusantara, 2026)
IoT-based Wireless Sensor Networks (WSN) are typically low-rate and latency-sensitive, making the selection of an efficient communication protocol critical. Unlike prior studies that generally examined a single aspect of ESP-NOW performance in isolation (range, comparison with Wi-Fi, or delay in multi-node scenarios), this study contributes a novel integrated evaluation framework that simultaneously analyzes ESP-NOW performance on ESP32 with a many-to-one topology across six operational variables: number of nodes (1–2), transmission interval (1, 3, and 5 seconds), transmission distance (10–50 meters), environmental condition (with and without obstacles), device positioning, and data load, while integrating the system end-to-end with an ESP32-based IoT gateway, InfluxDB time-series database, and real-time Grafana visualization. Each sensor node is equipped with a GY-BMP280 sensor for temperature and air pressure measurement. Performance was evaluated using TIPHON-standard Quality of Service (QoS) parameters, including delay, throughput, jitter, and packet loss, along with additional RSSI and power consumption measurements. Results show that a 1-second transmission interval yields the best QoS with delay <150 ms, jitter 0–75 ms, and 0% packet loss at distances up to 30 meters without obstacles. The IoT gateway successfully received data without packet loss under low-to-medium loads and demonstrated a write capacity to InfluxDB of up to 1000 data points per second. The main contribution of this study is the provision of a TIPHON-standardized ESP-NOW performance map and an end-to-end system architecture that can serve as a configuration reference for small-to-medium-scale IoT developers. This study is limited to a maximum of two nodes, so generalization to larger scales requires further investigation.